Photocatalytic degradation of ciprofloxacin antibiotic from aqueous solution by BiFeO3 nanocomposites using response surface methodology - R. Mostafaloo; M. Asadi-Ghalhari; H. Izanloo; A. Zayadi (Global Journal of Environmental Science and Management)
Ciprofloxacin antibiotic that is used to cure several kinds of bacterial infections have a high solubility capacity in water. The influent of ciprofloxacin to water resources in a low concentration affect the photosynthesis of plants, transforms the morphological structure of the algae, and then disrupts the aquatic ecosystem. 75% of this compound is excreted from the body down to the wastewater which should be removed. BiFeO3, a bismuth-based semiconductor photocatalyst that is responsive to visible light, has been recently used to remove organic pollutants from water. In this study, the optimal conditions for removing ciprofloxacin from aqueous solutions by the BiFeO3 process were investigated. Effective parameters namely pH, reaction time, ciprofloxacin initial concentration, BiFeO3 dose, and temperature on ciprofloxacin removal were studied by using response surface methodology. The validity and adequacy of the proposed model was confirmed by the corresponding statistics (i.e. F-values of 14.79 and 1.67 and p-values of 2 = 0.9107, R2adjusted = 0.8492, R2 predicted = 0.70, AP = 16.761). Hence the Ciprofloxacin removal efficiency reached 100% in the best condition (pH 6, initial concentration of 1 mg/L, BiFeO3 dosage of 2.5 g/L, reaction temperature of 30° C, and process time of 46 min).